Integrated Marketing Communication : Nusantara Coffee Brand Awareness On Oksigen Coffee - Lestari, Ratna Ayu; Khumayah, Siti; Lestari, Aghnia Dian (Jurnal Polisci, 2024)
Enjoying coffee in coffee shops has become an increasingly widespread culture in Indonesia. Oksigen Coffee is one of the manycoffee shops in Cirebon City. It was established in 2020 with a unique marketing style. Providing a variety of various variants of coffee, it is a place that many young people visit to adults and even families. This research aims to find out how Oksigen Coffee implements Integrated Marketing Communication (IMC) to increase brand awareness of Indonesian coffee in coffee shops. In this study, the author uses a descriptive qualitative approach that conducts direct interviews with the owner, marketing team, managers, baristas, and consumers of Oxygen Coffee. The theory used in this study is the theory of Integrated Marketing Communication. There are a few obstacles in marketing at Oxygen Coffee, namely fierce competition with other brands due to the rise of Coffee Shops in Cirebon City. Oksigen Coffee implements Advertising, Sales Promotion, Event and experience, Public Relations and publicity, Direct Marketing, Interactive Marketing, and Personal Selling successfully in creating an attractive environment for customers, thus strengthening its position in the local coffee industry in Cirebon City.